The Glycolytic Versatility of Bacteroides uniformis CECT 7771 and Its Genome Response to Oligo and Polysaccharides - Benítez-Páez, Alfonso; Gómez del Pulgar, Eva M.; Sanz, Yolanda (Frontiers in Cellular and Infection Microbiology, 2017)
Bacteroides spp. are dominant components of the phylum Bacteroidetes in the gut microbiota and prosper in glycan enriched environments. However, knowledge of the machinery of specific species isolated from humans (like Bacteroides uniformis) contributing to the utilization of dietary and endogenous sources of glycans and their byproducts is limited. We have used the cutting-edge nanopore-based technology to sequence the genome of B. uniformis CECT 7771, a human symbiont with a proven pre-clinical efficacy on metabolic and immune dysfunctions in obesity animal models. We have also used massive sequencing approaches to distinguish the genome expression patterns in response to carbon sources of different complexity during growth. At genome-wide level, our analyses globally demonstrate that B. uniformis strains exhibit an expanded glycolytic capability when compared with other Bacteroides species. Moreover, by studying the growth and whole-genome expression of B. uniformis CECT 7771 in response to different carbon sources, we detected a differential growth fitness and expression patterns across the genome depending on the carbon source of the culture media. The dietary fibers used exerted different effects on B. uniformis CECT 7771 activating different molecular pathways and, therefore, allowing the production of different metabolite types with potential impact on gut health. The genome and transcriptome analysis of B. uniformis CECT 7771, in response to different carbon sources, shows its high versatility to utilize both dietary and endogenous glycans along with the production of potentially beneficial end products for both the bacterium and the host, pointing to a mechanistic basis of a mutualistic relationship.